IMPLEMENTASI KEBIJAKAN PERMENDIKBUD NOMOR 23 TAHUN 2017 TENTANG HARI SEKOLAH - Rd. Siti Sofro Sidiq, Ria Septi Oktavia, Sujianto, (Jurnal Ilmu Administrasi Negara, 2019)
Implementation of Permendikbud Policy Number 23 Year 2017 Regarding SchoolDays. The purpose of this study was to determine the implementation of Permendikbud PolicyNumber 23 of 2017 concerning school days in SMP Negeri 4 Pekanbaru. This study uses theoriesfrom Edward III about policy implementation. This research was conducted using qualitativedescriptive methods. Research informants were the Head of the Pekanbaru Education Office,School Principals, Teachers, Students, Parents of Students, and School Committees. The samplingtechnique used was purposive sampling, with data collection using the method of observation,interviews and documentation. Data analysis through the process of collecting data, presentingdata and drawing conclusions. The results of this study indicate that the implementation ofPermendikbud policy No. 23 of 2017 concerning School Days (Case Study of SMP Negeri 4Pekanbaru) went as expected. In addition, it was also concluded that the implementation of a fullday school affects students, both positive and negative, and the impact is generally seen in schools.